Living with dams: managing the environmental impacts - McCartney, Matthew P. (IWA Publishing, 2009)
Dams, through disruption of physiochemical and biological processes, have water and associated environmental impacts that have far reaching social and economic consequences. The impact of each dam is unique. It depends not only on the dam structure and the attributes of local biota but also climatic and geomorphic conditions. Given the number of existing dams (over 45,000 large dams) and the large number that may be built in the near future, it is clear that humankind must live with the environmental and social consequences for many decades to come. This paper provides a review of the consequences for ecosystems and biodiversity resulting directly from the presence of dams on rivers, and of constraints and opportunities for environmental protection. It illustrates that a wide range of both technical and non-technical measures has been developed to ameliorate the negative impacts of dams. It argues that relatively few studies have been conducted to evaluate the success of these measures and that it is widely perceived that many interventions fail, either for technical reasons or as a consequence of a variety of socioeconomic constraints. It discusses the constraints to successful implementation and mechanisms for promoting, funding and ensuring compliance. Finally, it contends that there is a need to improve environmental practices in the operation of both existing and new dams.